Evaluation of the antioxidant, antidiabetic, and antiplasmodial activities of xanthones isolated from garcinia forbesii and their in silico studies - Wairata, Johanis; Sukandar, Edwin Risky; Fadlan, Arif; Purnomo, Adi Setyo; Taher, Muhammad; Ersam, Taslim (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Abstract: This study aimed to isolate xanthones from Garcinia forbesii and evaluated their activity in vitro and in silico. The isolated compounds were evaluated for their antioxidant activity by DPPH, ABTS and FRAP methods. The antidiabetic activity was performed against α-glucosidase and αamylase enzymes. The antiplasmodial activity was evaluated using Plasmodium falciparum strain 3D7 sensitive to chloroquine. Molecular docking analysis on the human lysosomal acid-alpha-glucosidase enzyme (5NN8) and P. falciparum lactate dehydrogenase enzyme (1CET) and prediction of ADMET for the active compound, were also studied. For the first time, lichexanthone (1), subelliptenone H (2), 12b-hydroxy-des-D-garcigerrin A (3), garciniaxanthone B (4) and garcigerin A (5) were isolated from the CH2Cl2 extract of the stem bark of G. forbesii. Four xanthones (Compounds 2–5) showed strong antioxidant activity. In vitro α-glucosidase test showed that Compounds 2 and 5 were more active than the others, while Compound 4 was the strongest against α-amylase enzymes. In vitro antiplasmodial evaluation revealed that Compounds 2 and 3 showed inhibitory activity on P. falciparum. Molecular docking studies confirmed in vitro activity. ADMET predictions suggested that Compounds 1–5 were potential candidates for oral drugs. The isolated 2–5 can be used as promising phytotherapy in antidiabetic and antiplasmodial treatment.